CULTURAL HERITAGE AND RELIGIOUS PRACTICES: THE ROLE OF PARTHIVAPURAM SREE PARTHASARATHI TEMPLE IN KANYAKUMARI DISTRICT - K, Santhosh Kumar; Thanammal, K.K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the Kanyakumari district, the Parthivapuram Sree Parthasarathi Temple is a representation of the rich religious and cultural legacy of South India. The temple, which was constructed under the Travancore kings’ control, is a striking example of Dravidian architectural genius and the region’s surviving spiritual culture. The temple, which is devoted to Lord Krishna, serves as a centre for community involvement and cultural preservation in addition to being a place of worship. This essay explores the temple’s artistic and architectural value, historical beginnings, and function in maintaining customary festivals and rituals. It draws attention to the temple’s role as a hub for classical dance and music, as well as its role in preserving old texts and promoting intercultural understanding. The socioeconomic effects of the temple are also examined, with a focus on how tourism and religious gatherings affect local livelihoods. The temple faces difficulties in this age of modernisation, including declining support and dangers to its customs. This essay emphasises how crucial it is to protect the Parthivapuram Temple as a living historical monument that represents the fusion of community, art, and spirituality. The temple is a symbol of cultural identity and solidarity in the Kanyakumari area because to its long-standing customs and ceremonies.